Scholarships of Emirs of Bukhara - Klichev, Oybek (Oriente moderno, 2020)
Based on the study of diplomatic correspondence between the Bukhara emirate and the Russian Empire, this article highlights the issues of granting scholarships issued at the expense of the Bukhara government to gifted and low-income students of secondary specialized, vocational educational institutions functioned in the regions of the Turkestan Governorate-General. Also, such important aspects of this problem as educational institutions that received scholarships of the Bukhara government, the conditions for their appointment, the size and terms of the scholarships, and the choice of scholarship holders, etc. were analyzed in detail.